(3TQM JYdje GdeJYdes - (3GdYKeGfj, GHf ESeGYjd, Rjf GdYQH, EHQGgje Hf ESeGYjd eMj GdOjf, cGf MjG (B996(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj CfYe YdjfG HCfhGY GdfYe hdWGFa GdEMSGf hHYO adeG QCjJ GdcJGH GdeSei HJYdje GdeJYde CQOJ Cf CTQMg TQMG jHjf ebGUOg hjcTa eYGfjg heHGfjg QLGA ef GdWGdHjf (B...s
(3BNQgG (B:s
(3aj cJGH GdeSei HWH GdfHj Udi Gddg Ydjg hSde (B... (3hgh cJGH eTghQ heYJHQ Hjf GdYdeGA adG HO dWGdH GdYde ef Gf jLOg hjJHQc HGdGKGQ hGdNHGQ GdePchQI ajg GdMeO ddg Ydi GdJeGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeWHhYGJ GdYQHjI (B1\11s
(3eYLe GdeWHhYGJ GdYQHjI (B1\11s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs